On the fiscal sustainability of Swiss Cantons since 1905 - Yannick Bury; Lars P. Feld; Ekkehard A. Köhler (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2023)
With an outstandingly long data set of Swiss cantonal public finances we study whether the Swiss subnational level runs sustainable fiscal policies. Going back to the year 1905, we test for stationarity of cantonal public debt, revenue and spending and for cointegration between cantonal revenues and expenditures. Based on time series properties, we estimate individual fiscal reaction functions for each canton and for the panel of cantons as a whole. Using second generation panel-modelling which accounts for heterogeneity in cantonal fiscal policy, structural breaks and cross-sectional dependence among the cantons, our results show that the cantons run sustainable policies. Moreover, our results provide evidence that fiscal institutions can explain part of the heterogeneity in cantonal fiscal reactions to increased debt.
Keywords: H62; H77; H72; C23; 330; Fiscal Sustainability; Fiscal Institutions; Swiss Cantons